2022
DOI: 10.1038/s41598-022-09809-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, in-silico, and in-vitro study of a new steroid derivative from Ophiocoma dentata as a potential treatment for COVID-19

Abstract: The medicinal potential of marine invertebrates' bioactive components that may act as anti-COVID-19 demonstrated promising results. Ophiocoma dentata, which is common in the Red Sea, is one such source. Therefore, this study aimed to isolate a new compound from the brittle star, Ophiocoma dentata, and evaluate its efficacy as anti-COVID-19 in-silico and in-vitro. Standard procedures were followed in order to assess the isolated compound’s preliminary toxicity and anti-inflammatory properties. Computer virtual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Interestingly, the three steroids that shared the stable binding had a characteristic hydroxylation pattern at positions 3, 5, and 6 in rings A and B. In addition, we have reported that the triterpene class of compounds, which is structurally related to compounds 5 , 7 , and 8 , is a promising scaffold to develop new M pro inhibitors [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the three steroids that shared the stable binding had a characteristic hydroxylation pattern at positions 3, 5, and 6 in rings A and B. In addition, we have reported that the triterpene class of compounds, which is structurally related to compounds 5 , 7 , and 8 , is a promising scaffold to develop new M pro inhibitors [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…56 The MultiTaskClassifier model is a fully connected deep residual network for multitask classification composed of preactivation residual blocks. Hyperparameterization for this first model was performed to optimize the best parameters, including layer size [256,256], [256,256,256], [256,256,256,256], dropout [0.0, 0.1], learning rate [0.005, 0.0035, 0.0025, 0.0010], number of epochs [5,10,20,30,40,50], momentum [0.0, 0.9], decay [0.0, 0.1], and batch size [32,64,128]. This was done using the GridHyperparamOpt optimizer, 67 the hyperparameter search method, 61 and the ROC-AUC metric.…”
Section: ■ Methodologymentioning
confidence: 99%
“…Ciclesonide is another inhaled corticosteroid which was tested in COVID-19 patients, but there are still insufficient evidences whether it is beneficial to COVID-19 patients or not [129] . Another new steroid 5α-cholesta-4(27),24-dien-3β,23β-diol was isolated from Ophiocoma dentata and studied against SARS-CoV-2 [130] . The invitro result shows that the new isolated steroid can are effective in 95% inhibition of the SARS-CoV-2 virus at 5 μg/ml concentration.…”
Section: Synthesis Of Glucocorticoidsmentioning
confidence: 99%